2021
DOI: 10.3390/ani11020355
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sugar Cane Molasses Addition on the Fermentation Quality, Microbial Community, and Tastes of Alfalfa Silage

Abstract: The objective was to study the effects of sugar cane molasses addition on the fermentation quality and tastes of alfalfa silage. Fresh alfalfa was ensiled with no additive (Control), 1% molasses (M1), 2% molasses (M2), and 3% molasses (M3) for 206 days. The chemical composition and fermentation characteristics of the alfalfa silages were determined, the microbial communities were described by 16S rRNA sequencing, and the tastes were evaluated using an electronic tongue sensing system. With the amount of added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 37 publications
(47 reference statements)
5
16
0
2
Order By: Relevance
“…The DM contents of fresh MS and LP were 23.48% DM and 30.6% DM, respectively. The CP content of MS was 23.3% DM, which was similar to the result (24.6% DM) of Luo et al (2021). The NDF (47.43% DM) and ADF (24.22% DM) contents of LP in our study were comparable to those reported by Li et al (2019), who reported that the NDF and ADF contents of annual ryegrass were 48.39% DM and 28.16% DM, respectively.…”
Section: Characteristics Of Raw Materialssupporting
confidence: 88%
“…The DM contents of fresh MS and LP were 23.48% DM and 30.6% DM, respectively. The CP content of MS was 23.3% DM, which was similar to the result (24.6% DM) of Luo et al (2021). The NDF (47.43% DM) and ADF (24.22% DM) contents of LP in our study were comparable to those reported by Li et al (2019), who reported that the NDF and ADF contents of annual ryegrass were 48.39% DM and 28.16% DM, respectively.…”
Section: Characteristics Of Raw Materialssupporting
confidence: 88%
“…Our research results on salinized silage microorganisms were different from those of previous studies. It has been reported that Lactococcus and Lactobacillus were the main genera of silage after ensiling [ 33 ]. Therefore, the role of LAB requires further research to determine whether Lactobacillus is suitable for the growth and reproduction of alfalfa in saline soil.…”
Section: Discussionmentioning
confidence: 99%
“…They can consume nutritional components, e.g., protein, and cause deterioration in the silages through oxidation-reduction reactions. However, the relative abundance of these undesired species were all less than 10%, which indicated that these undesirable microbes were suppressed by the LAB, leading to good conditions for long-term preservation (Luo et al 2021).…”
Section: Dynamic Changes In the Bacterial Diversity During Ensilingmentioning
confidence: 98%